Empowerment of Children in Dawung, Matesih, Karanganyar Village Through Educational Classes in the Time of Covid-19 - Abid Nurhuda; Afiffah Vinda Prananingrum (PT FORMOSA CENDEKIA GLOBAL, 2022)
One form of the implementation of Tri Darma in every university is that students are required to do Real Work Lectures (KKN). This program is a form of student service to the community which is carried out in a certain area in groups. but with the Covid-19, this service activity was transferred to their respective residences independently. The place of this research is Dukuh Sidewi RT 02/09 Dawung Village, Matesih, Karanganyar and aims to describe additional learning activities for local children in the Community Service Program through educational classes so that they do not only spend their time playing online games. The methods in this service are (1) Asking for permission to conduct KKN to the head of Dukuh Sidewi as a work partner. (2) Discuss the work program that has been prepared and adapted to the problems that exist in the children in the Dukuh Sidewi area. (3) Gathering the local hamlet children to make an educational class schedule. (4) Providing learning as well as assisting children through educational classes consisting of literacy classes, calligraphy classes, coloring classes, TPA and bilingual classes focusing on the Arabic language. The result of this service is that, with the existence of educational classes, the children become more focused in using their time, then become very spirit, enthusiastic and happy and there is an increase in the number of children at each meeting.